Arabinose assimilation defines a nonvirulent biotype of Burkholderia pseudomallei. - Smith, MD; Angus, B; Wuthiekanun, V; White, N (1997)
Two distinct types of Burkholderia pseudomallei, differentiated by the ability to assimilate L-arabinose but with similar morphologies and antigenicities, can be isolated from soil in Thailand. Approximately 25% of soil isolates from northeast Thailand were arabinose assimilators (Ara+), but in 1,200 sequentially studied patients, only arabinose "nonassimilators" (Ara-) caused melioidosis (P < 0.0001). In a murine model, there was a striking difference in virulence between Ara- and Ara+ B. pseudomallei. The mean (standard deviation) 50% lethal dose (LD[50]) inoculum for Ara- isolates was 182 (111) CFU/mouse compared with approximately 10(9) CFU/mouse for Ara+ soil isolates. There was no significant difference between the LD(50)s for clinical and soil Ara- isolates. All attempts to convert the biochemical phenotype by selective culture failed, which suggests that the biotype is stable.